Artificial Intelligence and the Environmental Crisis Can Technology Really Save the World?. - Skene, Keith, 1965- (Milton : Routledge, 2019)
A radical and challenging book which argues that artificial intelligence needs a completely different set of foundations, based on ecological intelligence rather than human intelligence, if it is to deliver on the promise of a better world. This can usher in the greatest transformation in human history, an age of re-integration. Our very existence is dependent upon our context within the Earth System, and so, surely, artificial intelligence must also be grounded within this context, embracing emergence, interconnectedness and real-time feedback. We discover many positive outcomes across the societal, economic and environmental arenas and discuss how this transformation can be delivered. Key Features: Identifies a key weakness in current AI thinking, that threatens any hope of a better world. Highlights the importance of realizing that systems theory is an essential foundation for any technology that hopes to positively transform our world. Emphasizes the need for a radical new approach to AI, based on ecological systems. Explains why ecosystem intelligence, not human intelligence, offers the best framework for AI. Examines how this new approach will impact on the three arenas of society, environment and economics, ushering in a new age of re-integration.
Section VIII: Imagining a New World -- VIII.1. The swallow whose nest was stolen: A salutary tale -- VIII.2. Blinded by the bling: Dashboard dogs and a disappearing sea -- VIII.3. What needs changed and what change do we need? -- VIII.4. The chains that bind: Taking responsibility for our footprints -- VIII.5. The Ogiek people and the new, improved invisible hand -- VIII.6. Lessons from the edge of the world: The St Kildan legacy -- VIII.7. The Garden of Eden complex: How not to fix the world -- VIII.8. The three cornerstones: Diversity, resilience and integration
Description based upon print version of record.
VIII.9. The central role of AI in feedback: Shaping our new world
OCLC-licensed vendor bibliographic record.
Keywords: COMPUTERS / General; COMPUTERS / Machine Theory; MATHEMATICS / Arithmetic; Environmental sciences -- Data processing; Artificial intelligence